Ambulatory blood pressure pattern in overweight and obese subjects: a prospective, cross-sectional study - Singh, Shuchi; Lohakare, Akash C. (International Journal of Research in Medical Sciences, 2019)
Background: Obesity is widely described as a leading cause of morbidity and mortality and is a known risk factor of many cardiovascular and non-cardiovascular diseases including hypertension. The aim of this study was to analyze the pattern of ambulatory blood pressure in overweight and obese subjects. Methods: This was a prospective, cross-sectional study performed over a period of 1 year in 95 subjects attending the Department of Medicine of tertiary care teaching institute. Anthropometric measures such as weight, height, body mass index (BMI), and waist circumference (WC) were recorded. Ambulatory blood pressure monitoring over a period of 24-hrs was performed in each individual and values were recorded. Comparison between normal subjects and overweight and/or obese subjects was done in terms of various ambulatory BP parameters. Results: Based on BMI, significantly higher proportion of females were obese (p-value = 0.020), as compared to males. Based on both BMI and WC, significant proportion of overweight and obese subjects had higher 24-hr SBP (p-value < 0.001) and 24-hr DBP (p-value = 0.001); higher day-time SBP (p-value < 0.001); higher night-time SBP (p-value < 0.001); and widening of 24-hr pulse pressure (> 50 mmHg) (p-value < 0.001) as compared to normal subjects. However, among various abnormal ABPM parameters, majority of the parameters revealed more incidence of BP abnormalities with increased BMI than with increased WC. Thus, BMI appeared to be a better anthropometric parameter than WC. Conclusions: The findings of the present study confirm that obesity in apparently non-hypertensive subjects leads to rise in both SBP and DBP. Moreover, it is the systolic part of ABPM which probably predicts the cardiovascular morbidity in overweight and obese subjects.